Evaluation of Intraocular Lens Tilt and Decentration in Congenital Ectopia Lentis by the Pentacam Scheimpflug System - Huiwen Ye; Zhenzhen Liu; Qianzhong Cao; Zhangkai Lian; Xinyu Zhang; Danying Zheng; Guangming Jin (Journal of Ophthalmology, 2022)
Purpose. The purpose of this study was to quantify the characteristics of the tilt and decentration of the IOL after trans-scleral suture fixation surgery in congenital ectopia lentis (CEL) patients. Methods. The clinical characteristics of 70 CEL patients at Zhongshan Ophthalmic Center in China were retrospectively analyzed. The tilt and decentration of intraocular lens (IOL) were measured by using a Pentacam and compared between different axial length (AL) subgroups. The correlation between IOL tilt, decentration, and ocular characteristics was investigated using Spearman’s correlation analysis. Results. The postoperative IOL position of CEL patients was mainly located nasally inferiorly. The average tilt of the IOL in CEL patients was less than 7° (for temporal: 2.21 ± 1.53°, for nasal: −1.84 ± 2.04°, for superior: 2.22 ± 2.18°, and for inferior: −1.70 ± 1.62°), and the average decentration of the IOL in CEL patients was larger than 0.4 mm (for temporal: 0.49 ± 0.38 mm, for nasal: −0.69 ± 0.46 mm, for superior: 0.72 ± 0.58 mm, and for inferior: −0.68 ± 0.54 mm). The decentration of CEL patients in the AL ≥ 26 subgroup was greater than those with AL < 24 mm and AL 24 to 26 mm subgroups (for superior: 0.72 ± 0.28 mm vs. 0.46 ± 0.25 mm and 0.48 ± 0.22 mm, all P<0.05; for inferior: -0.94 ± 0.56 mm vs. −0.44 ± 0.26 mm and -0.44 ± 0.46 mm, all P<0.05). IOL decentration was positively correlated with AL (for superior: r = 0.44, P=0.019; for inferior: r = 0.54, P=0.006). IOL tilt was positively correlated with AL on the superior side (r = 0.38, P=0.041). Conclusions. The extent of IOL decentration after trans-scleral suture fixation was great in CEL patients, and the IOL decentration in CEL patients was significantly associated with AL.